PENGARUH PROMOSI, TARIF, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN BERKUNJUNG (Studi Pada Pengunjung Plaplay Indoor Theme Park Kota Semarang) - Arum Jati, Theo Dora Sinta; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2020)
The decision to visit as a benchmark to find out the extent of the success of Plaplay Indoor Theme Park in Semarang City in the face of intense competition. This study aims to determine how the effect of promotion, tariffs, and service quality on the decision of visiting to the Plaplay Indoor Theme Park. The type of research used is explanatory research with a sample size of 100 respondents using incidental nonprobability sampling techniques. Data collection using a questionnaire and Google form with a Likert measurement scale. Data were analyzed using SPSS 21.0 for Windows. The results showed there was a promotion effect on the decision to visit with the value of t arithmetic (4.70)> t table (1.984), there was an effect of tariffs on the decision of visiting with a value of t arithmetic (6.081)> t table (1.984), there was an influence of service quality on the decision visited with the value of t arithmetic (9,266)> t table (1,6606), and there was an influence of promotion, tariffs and quality of service on the decision to visit with a calculated F value (41,137)> F table (3.09). Suggestions in this research are the use of Youtube and Instagram media for advertisements with youth nuanced material, increased frequency and short duration. Sales promotions ahead of and during holidays are increased. Directions to the location of the playground and supporting facilities are clarified. The quality of information services and the timeliness of processing ticket purchases are improved, and the number of janitors is added. By improving the quality of services above, it is expected that the tariffs imposed by Plaplay can be felt to be more adequate